2017
DOI: 10.1038/bdjopen.2017.18
|View full text |Cite
|
Sign up to set email alerts
|

What reward does a child prefer for behaving well at the dentist?

Abstract: Background:Paediatric dentists often report using positive reinforcement to encourage their young patients to show co-operative behaviour. For effective reinforcement to take place the reward should be salient to the individual. To date, there is little research into what reward a young patient will choose when attending the dentist.Aim:To identify what reward children between the age of 4–8 years will choose when attending the dentist, and to determine the extent of agreement between children and caregivers i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…In order to gain the cooperation of paediatric patients during dental care, it is important for dental practitioners to apply behavioural guidance (BG) techniques, such as those recommended by the American Academy of Pediatric Dentistry 4 . Various non‐pharmacological and pharmacological interventions have been found to be effective in guiding the behaviour of paediatric dental patients, resulting in an improved quality of patient management 5,6 . Dentists who demonstrate competence in communicating with patients and handling their emotional needs were found to have gained improved compliance in personal and professional oral health care 7 …”
Section: Introductionmentioning
confidence: 99%
“…In order to gain the cooperation of paediatric patients during dental care, it is important for dental practitioners to apply behavioural guidance (BG) techniques, such as those recommended by the American Academy of Pediatric Dentistry 4 . Various non‐pharmacological and pharmacological interventions have been found to be effective in guiding the behaviour of paediatric dental patients, resulting in an improved quality of patient management 5,6 . Dentists who demonstrate competence in communicating with patients and handling their emotional needs were found to have gained improved compliance in personal and professional oral health care 7 …”
Section: Introductionmentioning
confidence: 99%
“…We have progressed studies that have identified dentists' responses to explicit (e.g., crying) or nonexplicit (e.g., repeating words) emotions using an internationally recognized coding system named the Verona (VR) CoDES. 39 Frequently, the patient provides emotional hints -known as cues in the VR CoDES system -that may be explicit or nonexplicit and tend to be more common than overt emotional expressions. Emotional expressions are defined as concerns in the VR CoDES system.…”
Section: Evidence From Adult Patients' Dentistrymentioning
confidence: 99%
“…C-CBT involves computerized psychoeducation, v i r t u a l r e a l i t y t h e r a p y They are asked to rate their level of distress on the Subjective Unit of Distress Score (SUDS) ranging from 0 to 10 where 0 is "no discomfort" and 10 is "the worst distress experienced." 39 Each scenario is repeatedly presented to the patient until an SUDS of ≤ 2 is achieved, after which the next scenario is presented. Patients undergo exposure at their own pace and the duration of VRET is flexible based on the ability of patients to confront all the VR scenarios in a single visit.…”
Section: Vretmentioning
confidence: 99%
See 1 more Smart Citation